Creating an Inclusive Culture in Higher Education - Tikhomirova, Ekaterina; Shadrova, Ekaterina (International Dialogues on Education Journal, 2016)
In this article we present the results of implementing an international project aimed at creating and developing inclusive education in various partner countries. The authors demonstrate how participation in the project allowed us to arrange a number of events and activities at the Vologda State University (Russia) and to develop an inclusive culture in the largest institution of higher education in the region. The paper describes the main stages and practices of project implementation. The authors also present the questionnaires for university students and staff that may determine the level of inclusive culture in educational institutions. The pilot survey showed that the designed questionnaires might be used to assess the inclusive culture in different universities.